2007
DOI: 10.1002/pola.21913
|View full text |Cite
|
Sign up to set email alerts
|

Solvent‐free synthesis of pseudopolyrotaxane and polyrotaxane: Efficient threading complexation of a cyclodextrin wheel and a linear polymer axle to yield pseudopolyrotaxane and its fixation to polyrotaxane by the direct grinding of a solid mixture

Abstract: Pseudopolyrotaxane was obtained through the grinding of a mixture of O‐trimethyl‐α‐cyclodextrin and polytetrahydrofuran in a mortar by solvent‐free synthesis, and it was fixed to stable polyrotaxane by a successive end‐capping reaction with a bulky isocyanate by solid‐state grinding in a mortar. Higher molecular weight polytetrahydrofurans (Mn > 1000) successfully produced corresponding polyrotaxanes in moderate yields and with moderate coverage ratios. O‐Trimethyl‐β‐cyclodextrin and poly(ethylene glycol) also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 19 publications
2
23
0
Order By: Relevance
“…With the intriguing characteristics of free sliding and/or rotating of the threaded cyclic molecules, the polyrotaxanes have attracted increasing interests for their potential applications in smart materials, for example, stimuliresponsible supramolecular hydrogels, 4 slide-ring gels, 5,6 molecular machines, 7 carriers for drug delivery with hydrolysable bulky ends, 8 energy-transfer systems with modified CDs, 9 pH-/temperature-sensitive supramolecular micelles 10 and insulated molecular wires. 11 As for their preparation, a wide variety of strategies have been developed, [12][13][14] with a number of bulky groups such as naphthyl, 15 trinitrophenyl, 16 fluorescein-4-isothiocyanate 17 and 9-anthryl groups as the end stoppers. 18 However, oligomers or polymers of vinyl monomers have been rarely exploited as end stoppers of main-chain polyrotaxanes to our knowledge, 19,20 especially to do so via the atom transfer radical polymerization (ATRP).…”
Section: Introductionmentioning
confidence: 99%
“…With the intriguing characteristics of free sliding and/or rotating of the threaded cyclic molecules, the polyrotaxanes have attracted increasing interests for their potential applications in smart materials, for example, stimuliresponsible supramolecular hydrogels, 4 slide-ring gels, 5,6 molecular machines, 7 carriers for drug delivery with hydrolysable bulky ends, 8 energy-transfer systems with modified CDs, 9 pH-/temperature-sensitive supramolecular micelles 10 and insulated molecular wires. 11 As for their preparation, a wide variety of strategies have been developed, [12][13][14] with a number of bulky groups such as naphthyl, 15 trinitrophenyl, 16 fluorescein-4-isothiocyanate 17 and 9-anthryl groups as the end stoppers. 18 However, oligomers or polymers of vinyl monomers have been rarely exploited as end stoppers of main-chain polyrotaxanes to our knowledge, 19,20 especially to do so via the atom transfer radical polymerization (ATRP).…”
Section: Introductionmentioning
confidence: 99%
“…It was well known that both β‐CD and amphiphilic hyperbranched polymers can form inclusion complexations with guest molecules 22–24, 44–46. In this article, unique macromolecular structures of two β‐CD polymer brushes with amphiphilic hyperbranched polymer and β‐CD units were constructed and their detailed structures were also confirmed by FTIR, NMR, DSC and TGA measurements.…”
Section: Resultsmentioning
confidence: 81%
“…It is well known that β‐cyclodextrin (β‐CD) has a hydrophobic cavity that is lined with alkyl groups and glycosidic oxygen atoms and can act as a host for a variety of smaller molecular guests through noncovalent interactions 22–24. This means that β‐CD can be used as a functional material in biomedical and pharmaceutical industries 25, 26.…”
Section: Introductionmentioning
confidence: 99%
“…Under the driving of the hydrophobic interaction between the cyclodextrin and the polymer chain, DMBCD could increase the aqueous solubility of poly (tetrahydrofuran) (PTHF) or PPG diamine and formed solid inclusion complexes; TMBCD only formed solid inclusion complex with PTHF [4,5]. Takata and co-workers investigated the inclusion between TM-CD and some linear polymers under continue grinding without solvent [23]. TM-aCD could partly form inclusion complex with PTHF, and TM-bCD formed partial inclusion complex with PTHF or PEO with low efficiency, even under the action of external mechanical press.…”
Section: Inclusion Of Mbcd-ppo (Ppo M W * 425) and Inclusion Of Mbcd-htcmentioning
confidence: 98%
“…There were also some studies for this inclusion in solventfree condition. Liu et al [23] observed that part polymer chains could thread into the cyclodextrin cavities after grinding without any solvent for some time. And Balik and co-workers found that: the crystalline structure of native a-cyclodextrin could spontaneously transform from cage stack to column stack to some extent after mixed with liquid polyethylene glycol (PEG 200 or 400) and left in static [24,25].…”
Section: Introductionmentioning
confidence: 98%